Model Electronic Word Of Mouth dan Viral Marketing Pada Instagram dalam Mempengaruhi Minat Berkunjung Masyarakat di Wisata Alam Green Canyon Karawang Pada Masa Pandemi Covid-19 - Savitri, Citra; Hurriyati, Ratih; Wibowo, Lili Adi; Hendrayati, Heny (Business Education Program of Universitas Pendidikan Indonesia, 2022)
The Covid-19 pandemic have a negative impact on economic growth, including Indonesia. The tourism sector is one of the various sectors that have a negative impact on current conditions. Green Canyon is a reliable tourist destination in Kabupaten Karawang with a complete agreement of beauty and uniqueness. The role of social media in increasing business is a surefire strategy in increasing the number of visits. This research aims to determine the partial and simultaneous effect of Electronic Word Of Mouth and Viral Marketing on Interest in Visiting People on Instagram at Green Canyon Nature Tourism, Kabupaten Karawang. This research was conducted using quantitative descriptive. The samples used as many as 130 respondents using simple random sampling technique. Data analysis used was multiple regression with the help of SPSS application. The results of this research indicate that: Electronic Word Of Mouth and viral marketing on interest in visiting have agreed criteria based on the results and answers of respondents. Electronic Word Of Mouth and viral marketing on Visiting Interests have an effect partially or simultaneously.